Socialization of Indonesia Sustainable Palm Oil (ISPO) Certification Obligations for Smallholders Palm Oil Plantation in West Pasaman District - Novita, Nova (Asian Journal of Community Services, 2024)
This socialization aims to socialize the obligation of ISPO certification for independent oil palm farmers. This socialization activity was attended by Supervisors, Management, and representatives of the Heads of Farmer Groups of three Palm Oil Plantation Cooperatives in West Pasaman Regency, West Sumatra, Indonesia. The results of the socialization showed that most participants agreed to take part in certification as long as the government provided price guarantees and technical and financial support. The socialization results also show that with the current conditions, oil palm farmers in the three cooperatives still need to meet ISPO requirements. The concern of local governments and relevant palm oil organizations in providing technical and financial support will influence the achievement of the ISPO certification program targets, improve Indonesia's welfare, and enhance the image of Indonesia's sustainable palm oil.